Hubungan Motivasi Keluarga, Peran Bidan, Dan Efektivitas Antenatal Care Terhadap Pencegahan Tanda Bahaya Pada Ibu Hamil Di Poskesdes Desa Rajik Kecamatan Simpang Rimba Kabupaten Bangka Selatan : The Relationship between Family Motivation, the Role of Midwives, and the Effectiveness of Antenatal Care in Preventing Danger Signs in Pregnant Women at the Village Health Post, Rajik Village, Simpang Rimba District, South Bangka Regency - Yunita (Dohara POAJ, 2024)
Introduction: Pregnancy danger signals are symptoms that indicate possible risks that may arise during pregnancy or the prenatal period and can result in maternal death if not reported or detected. The aim was to find out the relationship between family motivation, the role of midwives, and the effectiveness of antenatal care on danger signs in pregnant women at the Poskesdes of Rajik Village, Simpang Rimba District, South Bangka Regency in 2022. Methods: This descriptive-analytic study used a quantitative method with a cross-sectional approach. The population is pregnant women using total sampling and the number of samples used is 50 people. The questionnaire is used as a research measurement tool. Data is processed using computer software. Results: The results of the analysis showed that of the 50 respondents, most of the respondents received warning signs of danger in pregnant women, namely as many as 26 respondents (52%); and most of the respondents received family motivation as many as 27 respondents (54%). most of the respondents got the midwife role. Meanwhile, there were 30 respondents (60%) who had good antenatal care effectiveness. the results of the Chi-Square statistical test obtained a p-value of 0,001 (p < 0,05) so can be concluded that there is a relationship between family motivation and prevention of danger signs in pregnant women. Discussion: There is a relationship between the role of the midwife and the prevention of danger signs in pregnant women (p-value = 0,019). there is a relationship between the effectiveness of antenatal care on the prevention of danger signs in pregnant women (p-value = 0,011). It is expected that pregnant women can increase counseling about the knowledge of pregnant women about the danger signs of pregnancy, especially midwives who actively provide counseling to increase the knowledge of pregnant women.